Impurity screening and stability of Fermi arcs against Coulomb and magnetic scattering in a Weyl monopnictide - Sessi, Paolo; Sun, Yan; Bathon, Thomas; Glott, Florian; Li, Zhilin; Chen, Hongxiang; Guo, Liwei; Chen, Xiaolong; Schmidt, Marcus; Felser, Claudia; Yan, Binghai; Bode, Matthias (Physical Review B, 2017)
We present a quasiparticle interference study of clean and Mn surface-doped TaAs, a prototypical Weyl semimetal, to test the screening properties as well as the stability of Fermi arcs against Coulomb and magnetic scattering. Contrary to topological insulators, the impurities are effectively screened in Weyl semimetals. The adatoms significantly enhance the strength of the signal such that theoretical predictions on the potential impact of Fermi arcs can be unambiguously scrutinized. Our analysis reveals the existence of three extremely short, previously unknown scattering vectors. Comparison with theory traces them back to scattering events between large parallel segments of spin-split trivial states, strongly limiting their coherence. In sharp contrast to previous work [R. Batabyal, Sci. Adv. 2, e1600709 (2016)2375-254810.1126/sciadv.1600709], where similar but weaker subtle modulations were interpreted as evidence of quasiparticle interference originating from Femi arcs, we can safely exclude this being the case. Overall, our results indicate that intra- as well as inter-Fermi arc scattering are strongly suppressed and may explain why - in spite of their complex multiband structure - transport measurements show signatures of topological states in Weyl monopnictides.
CRIS-Team Scopus Importer:2022-04-14